Management of gender dysphoria - Musa, Ramli; Amir Haszuwanni, Aida Farihah (CENTRIS, IIUM, 2024)
This chapters explores the management of gender dysphoria including biological, psychotherapy, and spiritual management. It also provides insights about the psychotherapy treatment on the problem. The research findings suggest that for transgender individuals in a Muslim country, a multifaceted approach is needed. This includes medical treatments,, spiritual guidance to instill positive religious practices, and social support from families and the broader community. At the same time avoiding judgment and providing understanding to help them navigate their situation.